MODIFICATION OF SCREEN PRINTED CARBON ELECTRODE USING ZNO NANOPARTICLE AND MOLECULARLY IMPRINTED POLYMER- POLY GLUTAMIC ACID (MIP(PGA)) FOR DETERMINATION OF SODIUM DODECYL SULFATE - Faradilla, Putri
Basically, surfactants are widely used in industry because they have advantages in terms of emulsions and dispersions. However, the use of excess surfactants will produce pollutants in the environment. One of the surfactants that pollutes the environment is sodium dodecyl sufate (SDS). SDS is a group of anionic surfactants that are widely found in household products, for example in detergents, floor cleaners, toothpaste, shampoo, and cosmetics. In the industry, SDS is used as a softener, color remover, and emulsifier. The use of SDS in excess levels will cause mild to serious skin irritation. Therefore, it is important to determine SDS in the environment. Some previous researches investigated SDS using GC-MS, fluorescence, colorimetry, and UV-Visible spectrophotometry with methylene blue reagent. However, the previous methods has disadvantage such as time consuming, expensive operational costs, and sample preparation using hazardous solvents. Recently, several works have developed analyzing of SDS using voltammetry techniques. Voltammetry technique provides several advantagous including the use of small amount of samples and chemicals, fast analysis, and simple analytical tools. In this study, a new electrochemical sensor for SDS determination has been developed using voltammetry techniques. The sensor is a modification of the screen-printed carbon electrode (SPCE) using ZnO nanoparticles and molecularly imprinted polymer (MIP) using glutamic acid as a functional monomer. Modification using ZnO nanoparticles, a semiconductor metal oxide, exhibit the electrochemical response. Similarly, MIP has a molecule template that provides a sensitive and selective response towards analyte. The ZnO / MIP modification on SPCE enhanced the current significantly due to the higher surface area generated from the ZnO nanoparticles. The modified electrodes were characterized using differential pulse voltammetry (DPV), cyclic voltammetry (CV), and SEM. The ZnO nanoparticles were synthesized using a chemical precipitation method. Based on the characterization results using particle size analysis (PSA) ZnO nanoparticles formed with a size of apprximately 72 nm. Characterization using UV-Visible spectrophotometer gave a strong absorbance peak against ZnO nanoparticles at 377 nm. MIP was produced by electropolymerization of glutamic acid which contains a template molecule, namely SDS. Electropolymerization was carried out using a cyclic voltammetry technique of 15 cycles The extraction of analyter from polymer matrix was carried out using the CV technique in ultrapure water for 5 cycles. Under optimal conditions, the performance of CPE/nZnO/MIP towards SDS